Peran dan Kedudukan KUA dalam Pengajuan Pembatalan Perkawinan Akibat Pemalsuan Identitas (Putusan 2856/Pdt.G/2022/PA. Mdn) - Suryaningsih, Fitri Sri; Hayati, Amal (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This study aims to examine the role and position of the KUA when submitting an annulment of a marriage due to falsification of identity in the decision 2856/Pdt.G/2022/PA. Mdn. Where usually those who file lawsuits for annulment of marriages are husbands, wives or relatives who get married because there are parties who feel cheated. What is unique is the decision number 2856/Pdt.G/2022/PA. Mdn. is that the plaintiff filing a lawsuit for annulment of the marriage is the KUA itself. This research is a normative juridical research, with a statutory and conceptual approach. The results of the study described that the KUA was less thorough in examining the identity documents of the prospective bride and groom. And the KUA also filed a lawsuit for annulment of the marriage to the Religious Court, even though juridically it is very permissible. So that the role and functions of the KUA are really needed which can actually be carried out according to the applicable procedures, namely to help carry out some of the district ministry of religion offices in the field of Islam in the sub-district area. This study concluded that the head of the KUA made a mistake and filed a lawsuit for annulment of his marriage to the Medan Religious Court. Juridically, this is perfectly permissible. however, this is a very unique and rare occurrence. And the steps of the KUA in submitting the application are correct, here the KUA as a marriage registrar, issues a marriage book, supervises marriages in accordance with Article 1 PERMA No. 19 of 2018 concerning registration of marriages.